Gas plasma-spurred wound healing is accompanied by regulation of focal adhesion, matrix remodeling, and tissue oxygenation - Anke Schmidt; Grit Liebelt; Felix Nießner; Thomas von Woedtke; Sander Bekeschus (Redox Biology, 2021)
In response to injury, efficient migration of skin cells to rapidly close the wound and restore barrier function requires a range of coordinated processes in cell spreading and migration. Gas plasma technology produces therapeutic reactive species that promote skin regeneration by driving proliferation and angiogenesis. However, the underlying molecular mechanisms regulating gas plasma-aided cell adhesion and matrix remodeling essential for wound closure remain elusive. Here, we combined in vitro analyses in primary dermal fibroblasts isolated from murine skin with in vivo studies in a murine wound model to demonstrate that gas plasma treatment changed phosphorylation of signaling molecules such as focal adhesion kinase and paxillin α in adhesion-associated complexes. In addition to cell spreading and migration, gas plasma exposure affected cell surface adhesion receptors (e.g., integrinα5β1, syndecan 4), structural proteins (e.g., vinculin, talin, actin), and transcription of genes associated with differentiation markers of fibroblasts-to-myofibroblasts and epithelial-to-mesenchymal transition, cellular protrusions, fibronectin fibrillogenesis, matrix metabolism, and matrix metalloproteinase activity. Finally, we documented that gas plasma exposure increased tissue oxygenation and skin perfusion during ROS-driven wound healing. Altogether, these results provide critical insights into the molecular machinery of gas plasma-assisted wound healing mechanisms.